Reliability of pain assessment by parents and attending emergency medical officers of pediatric patients presenting with acute pain at emergency department Hospital Universiti Sains Malaysia Kubang Kerian, Kelantan - Sarah, Shaikh Abdul Karim (2008)
Pain assessment is the first step towards effective analgesic methods. This is because pain is an individualized sensation and emotion. Objective of this study is to assess the agreement of pain severity assessment done by parents or guardians and attending emergency medical officers in a child in terms of inter-rater agreement between parents or guardians, attending EDMO and respective child-patients in pain. This is a single centre cross-sectional study carried out from August 2006 till August 2007 in Emergency Department Hospital Universiti Sains Malaysia Children between the age of 5 till 15 years old with complaint of acute pain from either trauma or medical causes were enrolled. They were administered either Faces Pain Scale - Revised or Visual Analog Scale for self assessment of pain. Their accompanying parents or guardians and attending Emergency Medical Officers (EDMO) blinded to one another were given Visual Analog Scale to assess respective childpatients pain. The scores obtained was then analyzed to obtain the Kappa value for agreement between the self assessments by the child-patients with that of parents or guardians and attending ED MOs. A total of 118 child-patients were recruited from August 2006 to August 2007. Mean pain score by child-patients is 5.6 (SD ±2.7). Mean pain score by parents or guardians was 5.3(SD ±2.16) and by attending EDMO 4.5 with (SD ±2.19). Kappa value of agreement between pain assessment by parents or guardians with respective child is 0.16 and that between attending EDMO with respective child-patient is 0.11. The study showed that both accompanying parents or guardians and attending EDMOs have poor level of agreement in severity of pain assessment compared to self assessment by respective child-patients. The level of agreement is good in children above 10 years of age and with traumarelated pain.